Design and Development of Check Valve for Irrigation Pump - Maniruzzaman, M; Islam, A K M S; Alam, M M (Bangladesh Rice Journal, 2023)
Shallow tube wells (STW) are widely operated in Bangladesh to draw groundwater for irrigating the crop field. About 65% of irrigated area is covered by more than 1.3 million STW. However, farmers are facing difficulties in starting STW due to priming problem. Therefore, this study was undertaken to design and develop a check valve (CqV)/non-return valve to overcome the priming problem as well as reduce the drudgery of farmers while starting STW. The check valve was designed based on the working principles of hand tubewell operating system. Considering the tubewell size of 100 mm, check valve having three diameters of 125 mm, 150 mm, and 175 mm for two-valve fitting lengths of 150 mm and 225 mm based on the flange or thread joint were fabricated using locally available material at Bangladesh Rice Research Institute (BRRI) research workshop. Check valves were tested at the field level in different locations of Bangladesh. The results revealed that the field performance of check valve overcame the priming problem, made easy starting and reduced the drudgery of farmers. The best performance was found when the diameter of the cheque valve was at least 50 mm over the size of tube well and the minimum length was 150 mm. The installation of check valve could not create any adverse effects on tube well discharge and engine revolution per minute (RPM). It could successfully reduce the starting time and facilitate the easy use of plastic pipe/ polythene pipe, which reduces the water conveyance loss and pumping hours. Bangladesh Rice J. 25 (2) : 77-84, 2021